Analisis Dan Perancangan User Interface Sistem Informasi Pembayaran Mahasiswa STMIK Primakara Berbasis Web - Mentayani, Ni Putu Anik; Satwika, I Putu; Pramesti Dwi Putri, I Gusti Agung; Paramitha, A.A Istri Ita; Tiawan, Tiawan (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2022)
The Marketing Division and the Finance Division of STMIK Primakara still have problems in the process of recording student payments. The problems faced by the finance division at STMIK Primakara are piling up DPP payment invoices, the existence of new prospective students who defer DPP fees for too long, miscommunication regarding who the DPP recipient is after the DPP is suspended for too long, and the absence of appropriate information for students to know the remaining payments. both DPP, Orientation and Tuition Payments. This study aims to determine the analysis and design of a Web-Based User Interface for STMIK Primakara Student Payment Information System in order to facilitate computerized payments for new students and student enrollments of STMIK Primakara students. The method used is the Software Development Life Cycle (SDLC) method using the Prototype Model. Keywords: System Design, Student Payments, SDLC Prototype Model Method.